The Boracay closure: Socioeconomic consequences and resilience management - Celia M. Reyes; Jose Ramon G. Albert; Francis Mark A. Quimba; Ma. Kristina P. Ortiz; Ronina D. Asis (Philippine Institute for Development Studies (PIDS), 2018)
For many years, the Boracay island in the province of Aklan has been a favorite tourist destination in the country. The increasing influx of both international and local tourists, coupled with the improper management of wastes and poor implementation of environmental policies and guidelines, has aggravated the island's environmental condition and sustainability. This year, the government has decided to close down the island to address these critical concerns. This study looks into the potential economic effects of this recent directive, which is intended to last for six months from May to October 2018. Using secondary data, the study employs an Input-Output and computable general equilibrium (CGE) model analyses. Three scenarios, which are based on different percentage reductions in the Philippine tourism receipts, are examined to look at the projected losses in total output and compensation, as well as its effects on specific economic sectors. Results show that the aggregate economic loss in total output would range from PHP20.8 billion to PHP83.15 billion, while in terms of income, the loss in compensation would range from PHP 7 billion to PHP 27.9 billion. Tourism sectors would be most affected, as well as agriculture and services, albeit slightly. Overall, while the results may not be very significant at the national level, it will still have its direct and indirect effects to people living in the island and in the entire municipality of Malay. The study recommends the need to craft strategic and harmonized overall plan which lays out the various government efforts to safeguard the welfare of those who will be severely affected by the sudden closure of Boracay.
Keywords: 330; Boracay closure; environmental sustainability; Philippine tourism; input-output analysis; computable general equilibrium